2021
DOI: 10.3390/ma14071772
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Fillers and Rapeseed Oil-Based Polyol as Natural Raw Materials for the Production of Rigid Polyurethane Foams

Abstract: The reported study concerns the introduction of renewable raw materials into the formulation of rigid polyurethane foams in the quest for the sustainable development of polymer composites. In this study, rigid polyurethane foam composites were prepared using 75 wt.% of rapeseed oil-based polyol and 15 parts per hundred parts of polyol (php) of natural fillers such as chokeberry pomace, raspberry seeds, as well as hazelnut and walnut shells. The influence of the used raw materials on the foaming process, struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…The studies on the effect of specific fillers such as cellulose [ 38 ] on the cell structure of PUR foam composites show that the introduction of the filler into a PUR system reduced the size of the cells ( Figure 1 c,e). These results were found to be in agreement with the studies carried out by Leszczyńska et al [ 39 ], who demonstrated a reduction in cell size after the incorporation of vegetable-based fillers. The smaller cell size could have effectively extended the heat transfer path through the solid phase and reduced the radiant heat transfer, thus, lowering the thermal conductivity values of the non-flame retardant and flame retardant PUR foam composites with the SFP and SFP/LG fillers.…”
Section: Resultssupporting
confidence: 93%
“…The studies on the effect of specific fillers such as cellulose [ 38 ] on the cell structure of PUR foam composites show that the introduction of the filler into a PUR system reduced the size of the cells ( Figure 1 c,e). These results were found to be in agreement with the studies carried out by Leszczyńska et al [ 39 ], who demonstrated a reduction in cell size after the incorporation of vegetable-based fillers. The smaller cell size could have effectively extended the heat transfer path through the solid phase and reduced the radiant heat transfer, thus, lowering the thermal conductivity values of the non-flame retardant and flame retardant PUR foam composites with the SFP and SFP/LG fillers.…”
Section: Resultssupporting
confidence: 93%
“…J. Lisperguer et al obtained a degradation peak for tannin obtained from Acacia dealbata at 258 °C [ 48 ]. The chemical composition of this specific CP (with no purification) was determined in the previous report by researchers from the Warsaw University of Technology [ 49 ]. Table 7 shows the content of cellulose, hemicellulose, lignin, and raw fat in CP filler.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, the global polyurethane (PUR) market was estimated to be worth $95.13 billion and is forecast to increase at an annual rate of 12% up to $149.91 billion by 2023. PUR foams have a share of 67% and dominate the PUR market [1].…”
Section: Introductionmentioning
confidence: 99%